Prophetic Leadership in the Battle of Hunain: Strategic Lessons for Modern Leadership - Dewi, Siska; Naimah; Jannah, Jessika Ahali; Istiqomah, Nurul; Oktavianti, Mutia (LifeSciFi, 2025)
The Battle of Hunain is one of the important events in Islamic history that proves the leadership of The Prophet Muhammad SAW in facing a major crisis. This study aims to analyse the leadership strategy of the Prophet Muhammad SAW in the Battle of Hunain and its relevance to the concept of contemporary leadership. The method used is qualitative with a literature study approach sourced from hadith books, Sirah Nabawiyah, and academic literature. The results of the study show that The Prophet SAW implemented a leadership strategy based on vision, exemplary behaviour, crisis management, and effective situational adaptation. Decisiveness in decision making, the ability to raise the spirit of the troops, and anxiety in facing changes in the war situation are the main keys to victory. Strategies such as intelligence gathering, logistics planning, and reorganizing troops during chaos are proof of his capacity as a visionary and transformational leader. The moral and spiritual values ​​inherent in the leadership of The Prophet strengthen his relevance as an ideal leadership model in various modern contexts, including organizations, education, and government.